{x4+5y=6(1)x2y2+5x=6(2)Trừ phương trình thứ nhất cho phương trình thứ hai ta có x4−x2y2+5y−5x=0⇒x2(x2−y2)−5(x−y)=0⇒(x−y)(x2(x+y)−5)=0⇒x=y hoặc x2(x+y)=5Nếu x=y⇒x4+5x−6=0⇒(x−1)(x+2)(x2−x+3)=0 ⇒x=1,−2 Nếu x2(x+y)=5Từ (1),(2) ta suy ra 5x≤6,5y≤6⇒x,y≤65Suy ra x2(x+y)≤3625.125=3,456 Nhỏ hơn 5Vậy Trường hợp này vô nghiệm
{x4+5y=6(1)x2y2+5x=6(2)Trừ phương trình thứ nhất cho phương trình thứ hai ta có
x4−x2y2+5y−5x=0⇒x2(x2−y2)−5(x−y)=0⇒(x−y)(x2(x+y)−5)=0⇒x=y hoặc
x2(x+y)=5Nếu
x=y⇒x4+5x−6=0⇒(x−1)(x+2)(x2−x+3)=0 ⇒x=1,−2 Nếu
x2(x+y)=5Từ
(1),(2) ta suy ra
5x≤6,5y≤6⇒x,y≤65Suy ra
x2(x+y)≤3625.125=3,456 Nhỏ hơn
5Vậy Trường hợp này vô nghiệm